Cost analysis of botulinum therapy of spastic forms of cerebral palsy in Ukraine - S. O. Soloviov; O. V. Nazar; M. V. Leleka (Фармацевтичний журнал, 2021)
Cerebral palsy (CP) represents a group of disorders of the mechanisms of movement and body position, causing limitations of activity, which are caused by non-progressive damage to the developing brain, fetus or child. About 80% of cases are spastic forms of cerebral palsy. Along with motor rehabilitation, the use of botulinum toxin type A (BoNT-A) is considered one of the main methods of treatment of choice for focal spastic and dystonic syndromes, regardless of their etiology. At present, there are no studies in Ukraine on the analysis of the costs of using drugs based on BoNT-A, taking into account the recommended dose and frequency of administration.